Dealing with the costs of the COVID-19 pandemic – what are the fiscal options? - Gene Ambrocio; Mikael Juselius (Bank of Finland, 2020)
The main problem facing policymakers during the corona virus pandemic is how to mitigate its humanitarian and economic costs. Doing so invariably involves trading off some costs against others as well as short-term against longer-term consequences. We provide an overview of economic literature that is relevant for understanding these trade-offs in the context of the current pandemic. We also discuss a range of fiscal measures that can be adopted with the aim of achieving the preferred trade-offs at lowest cost.
urn:nbn:fi:bof-202004092069
Keywords: H12; H81; I18; 330; pandemics; economic costs; COVID-19; fiscal policy